2015
DOI: 10.1007/s00068-015-0575-z
|View full text |Cite
|
Sign up to set email alerts
|

Non operative management of blunt splenic trauma: a prospective evaluation of a standardized treatment protocol

Abstract: The non operative management of blunt splenic trauma, according to our protocol, represents a safe and effective treatment for both minor and severe injuries, achieving an overall success rate of 95 %. The angiographic study could be indicated both in patients with CT evidence of vascular injuries and in patients with high-grade splenic injuries, regardless of CT findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 32 publications
4
33
1
Order By: Relevance
“…In another study serial CEUS follow-up examinations in a few patients with mild liver and spleen trauma were performed and CEUS was considered to be particularly suited to the follow-up of this kind of lesion [16]. As in some other previous studies, we reported a very low NOM failure rate [14,15,17] and this could be related to the high rate of blunt abdominal trauma with splenic injury that underwent splenic angioembolization after the CT performed in the ED in our cohort. In fact, a previous study demonstrated that high splenic angioembolization rates could reduce NOM failure [18].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…In another study serial CEUS follow-up examinations in a few patients with mild liver and spleen trauma were performed and CEUS was considered to be particularly suited to the follow-up of this kind of lesion [16]. As in some other previous studies, we reported a very low NOM failure rate [14,15,17] and this could be related to the high rate of blunt abdominal trauma with splenic injury that underwent splenic angioembolization after the CT performed in the ED in our cohort. In fact, a previous study demonstrated that high splenic angioembolization rates could reduce NOM failure [18].…”
Section: Discussionsupporting
confidence: 67%
“…injuries, particularly in hemodynamically stable patients with isolated blunt low or moderate-energy abdominal trauma [8][9][10][11]. Some previous studies showed that CEUS can detect active bleeding [12,13] and that performing one or two CEUS during follow-up is useful [14,15]. In another study serial CEUS follow-up examinations in a few patients with mild liver and spleen trauma were performed and CEUS was considered to be particularly suited to the follow-up of this kind of lesion [16].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, as the quality of non‐operative management (NOM) has developed, blunt injuries to visceral organs such as spleen, liver, or kidney are tending to be managed non‐operatively with a high rate of success 1, 2, 3. However, NOM of these injuries sometimes leads to critical delayed complications and the possibility of lethal damage for the patients 4.…”
Section: Aimmentioning
confidence: 99%
“…31 Within the abdomen, pseudoaneurysms are most frequently encountered in the spleen, since this is the most commonly injured abdominal organ in blunt trauma. 5,43 An accurate identification is crucial, since angiographic embolization is the treatment of choice (Figures 4-6). 5,25,43 MDCT protocol should include an arterial phase, 1,14,25,43 since it allows the detection of AVF and improves the detection of pseudoaneurysm in the spleen ( Figure 5).…”
Section: Pseudoaneurysmsmentioning
confidence: 99%
“…5,43 An accurate identification is crucial, since angiographic embolization is the treatment of choice (Figures 4-6). 5,25,43 MDCT protocol should include an arterial phase, 1,14,25,43 since it allows the detection of AVF and improves the detection of pseudoaneurysm in the spleen ( Figure 5). 14,24 The arterial phase allows the identification of the circumscribed area of medium contrast attenuation with the wash in and washout similar to those of the contiguous artery; however, in the portal venous phase, the attenuation is similar to the parenchyma.…”
Section: Pseudoaneurysmsmentioning
confidence: 99%